2021
DOI: 10.3389/fpubh.2021.586389
|View full text |Cite
|
Sign up to set email alerts
|

Correlations Between Cognitive Functions and Clinical Symptoms in Adolescents With Complex Post-traumatic Stress Disorder

Abstract: Introduction: Complex post-traumatic stress disorder (C-PTSD) is characterized by the typical symptoms of PTSD, in addition to affective dysregulation, negative self-concept, and disturbances in interpersonal relationships. Children and adolescents with C-PTSD have been reported to have deficits in emotional and cognitive functions. We hypothesized that the following are associated with the severity of C-PTSD symptoms: (1) adolescents with C-PTSD who show deficits in emotional perception and cognitive function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 41 publications
1
10
0
1
Order By: Relevance
“…In terms of symptom assessments, most studies used the Dissociative Experiences Scale (DES) (Carlson et al, 1993) or its subscale (i.e., DES-Taxon; DES-T) (Waller & Ross, 1997) to assess dissociation ( n = 13) (Dorahy et al, 2013; Dorrepaal et al, 2012; Ford et al, 2015; Ford et al, 2017; Hyland et al, 2018; Longo et al, 2019; Peles et al, 2012, 2014; Powell, 1996; Sachsse et al, 2006; Tian et al, 2020; Van Dijke et al, 2015; Zucker et al, 2006). Most studies used the International Trauma Questionnaire (ITQ) (Cloitre et al, 2018) ( n = 11) or the Structured Interview for Disorders of Extreme Stress (SIDES) (Pelcovitz et al, 1997) ( n = 6) to assess CPTSD symptoms; only nine studies used other methods (e.g., clinical assessment, the Stress Reactions Checklist for Disorders of Extreme Stress, the C-PTSD Interview Scale) to assess CPTSD symptoms (Dorahy et al, 2013; Ford et al, 2015, 2017; Haselgruber et al, 2020; Longo et al, 2019; Powell, 1996; Powers et al, 2017; Sachsse et al, 2006; Shin et al, 2021). As long as the study explained how dissociation and CPTSD were specifically assessed (e.g., which measure was used, or how clinical assessment was conducted), it was regarded as meeting the second inclusion criterion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of symptom assessments, most studies used the Dissociative Experiences Scale (DES) (Carlson et al, 1993) or its subscale (i.e., DES-Taxon; DES-T) (Waller & Ross, 1997) to assess dissociation ( n = 13) (Dorahy et al, 2013; Dorrepaal et al, 2012; Ford et al, 2015; Ford et al, 2017; Hyland et al, 2018; Longo et al, 2019; Peles et al, 2012, 2014; Powell, 1996; Sachsse et al, 2006; Tian et al, 2020; Van Dijke et al, 2015; Zucker et al, 2006). Most studies used the International Trauma Questionnaire (ITQ) (Cloitre et al, 2018) ( n = 11) or the Structured Interview for Disorders of Extreme Stress (SIDES) (Pelcovitz et al, 1997) ( n = 6) to assess CPTSD symptoms; only nine studies used other methods (e.g., clinical assessment, the Stress Reactions Checklist for Disorders of Extreme Stress, the C-PTSD Interview Scale) to assess CPTSD symptoms (Dorahy et al, 2013; Ford et al, 2015, 2017; Haselgruber et al, 2020; Longo et al, 2019; Powell, 1996; Powers et al, 2017; Sachsse et al, 2006; Shin et al, 2021). As long as the study explained how dissociation and CPTSD were specifically assessed (e.g., which measure was used, or how clinical assessment was conducted), it was regarded as meeting the second inclusion criterion.…”
Section: Resultsmentioning
confidence: 99%
“…All studies were published during 2006-2021, except for the thesis identified from ProQuest (Powell, 1996). Most studies used adult samples (n = 23), and only three studies recruited children as participants (Haselgruber et al, 2020(Haselgruber et al, , 2021Shin et al, 2021). Participants were from different countries/regions, including the United States (n = 5), the United Kingdom (n = 4), the Netherlands (n = 3), Austria (n = 2), Canada (n = 2), Ireland (n = 2), South Korea (n = 2), and one in each of the additional countries-Australia, China, Denmark, Germany, Israel, and Italy.…”
Section: Study Characteristics and Designsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alguns estudos mostraram que adolescentes com TEPT-complexo têm uma taxa maior de história de agressão sexual, dissociação e automutilação do que adolescentes com TEPT (Shin et al, 2021).…”
Section: Resultsunclassified
“…Given emotion dysregulation is a DSO symptom of CPTSD, exploring associations between CPTSD and EFs could inform understanding of the disorder and how existing PTSD interventions could be tailored to improve treatment response in veterans seeking treatment for CPTSD. In a study using an adolescent sample, deficits in EFs were associated with greater CPTSD severity [ 36 ]. However, less is known about the relationship between CPTSD and EFs in veteran populations.…”
Section: Introductionmentioning
confidence: 99%